Comparative study of ultrasonography and computed tomography for detecting stones in case of renal colic - Manandhar Dwa, Yogita; Shrestha, Shreejana; Jaiswal, Pooja; Maharjan, Dinesh (Journal of Patan Academy of Health Sciences, 2025)
Introduction: Nephrolithiasis is most common cause of renal colic encountered. Computed Tomography of kidneys, ureters and bladder (CT-KUB) was found to be extremely sensitive and specific for ureteric calculi. This study aimed to compare the diagnostic performance of ultrasonography ( USG) and CT-KUB in patients presenting with renal colic based on previous studies by Sharad Kondekar, Iqbal Minne & Doaa N Anas, Khaled Elshafey et.al. Method: This is a retrospective study. The USG and CT-KUB findings of 2574 patients were retrospectively analyzed over four years. The data was compiled using XLSX Spreadsheet. Sensitivity, specificity, diagnostic accuracy, positive predictive value and negative predictive values of USG were calculated taking CT-KUB as the gold standard. Result: In 2574 sets of data, the majority of patients were ≤ 30 years old with males predominating. In 2269 cases, renal calculi were detected in both USG and CT-KUB and CT-KUB alone detected renal calculi in 2554 cases. USG detected maximum 1435 cases with 5-10mm sized renal calculi and CT-KUB too detected maximum of 5-10 mm calculi in 1430 cases. The sensitivity, specificity, diagnostic accuracy, positive predictive value and negative predictive values of USG taking CT-KUB as the gold standard, were 88.21%, 17.6%. 87.75%, 99.38% and 0.98% respectively. Conclusion: Although CT-KUB exposes patients to ionizing radiation, it remains the gold standard due to its higher diagnostic accuracy. USG, while less specific, may serve as an initial, no-invasive screening tool.